2006
DOI: 10.1007/s11186-006-9005-x
|View full text |Cite
|
Sign up to set email alerts
|

Third parties and status position: How the characteristics of status systems matter

Abstract: For organizations, as for individuals, status position governs access to a variety of valued rewards. To uncover the causes of status position, recent research has focused on the relationship between the attributes of individual organizations and their standing in a status hierarchy. Although this research has made valuable contributions to our understanding of both the consequences of status to organizations and the determinants of status, its emphasis on organizational attributes has not addressed how the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 29 publications
1
64
0
1
Order By: Relevance
“…Such findings suggest that processes of interpersonal evaluation and status conferral are dependent not only on structural and contextual features of the status system (see Sauder 2006) but also the properties of the particular actors being evaluated at a given time. The way in which doormen evaluated worth and conferred status varied by a) the constellation of cues displayed by a specific actor, and b) the meanings they attributed to a given level of a cue for members of a particular social group.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings suggest that processes of interpersonal evaluation and status conferral are dependent not only on structural and contextual features of the status system (see Sauder 2006) but also the properties of the particular actors being evaluated at a given time. The way in which doormen evaluated worth and conferred status varied by a) the constellation of cues displayed by a specific actor, and b) the meanings they attributed to a given level of a cue for members of a particular social group.…”
Section: Discussionmentioning
confidence: 99%
“…This paper thus provides empirical support for the resource-based assumptions underlying previous qualitative and conceptual work, which has analyzed the strategic and organizational responses of universities to ranking systems (e.g., Elsbach and Kramer 1996;Espeland and Sauder 2007;Sauder and Fine 2008). Reputation is clearly an organizational resource in higher education that has been, and is increasingly defined by, the formal structure of rankings (Bastedo and Bowman 2010;Sauder 2006). The results described here allow us to go further to specify the organizational conditions under which rankings can be predicted to influence varying resource flows.…”
Section: Discussionmentioning
confidence: 60%
“…From an institutional perspective, rankings constitute a third-party status system that form a significant part of the normative environment of universities (Rao 1994;Sauder 2006). Powerful institutional effects are created by third-party organizations in the organizational field, especially those that seek to measure and evaluate others from whom they have organizational distance.…”
Section: Institutional Accountsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bastedo and Bowman (in press) have shown that college rankings affect college deans' and presidents' perceptions of institutional quality. In addition, rankings have a strong influence on internal decision making at professional schools, since administrators are sensitive to the strong reaction to various rankings within their own markets (Elsbach and Kramer 1996;Espeland and Sauder 2007;Sauder 2006). Decision theory, however, would suggest that these high-level administrators are much less likely than students and parents to be persuaded, since administrators possess a great deal of information about peer institutions, and many of them believe the rankings are quite flawed (Finder 2007).…”
Section: Specific Attitudes Toward College Choicementioning
confidence: 99%